Flexibility in Existential Beliefs and Worldview: Testing Measurement Invariance and Factorial Structure of the Existential Quest Scale in an Italian Sample of Adults - Rizzo, Marco; Testa, Silvia; Gattino, Silvia; Miglietta, Anna (Frontiers in Psychology, 2019)
The aim of the present study was to assess the psychometric properties of the Existential Quest Scale (EQ), an instrument developed to assess openness to changing one’s own convictions concerning existential issues. We developed the Italian version of the scale and examined factorial structure, internal consistency, discriminant validity and measurement invariance across gender and age groups. A total of 291 Italian adults were recruited, and they completed a self-report questionnaire comprising measures of authoritarianism, cognitive closure, well-being and religiousness, alongside the EQ. Confirmatory factor analysis showed that the original one-factor structure was replicated in this study, except for one item. The internal consistency of the eight-item scale (α = .70) and the discriminant validity were in line with those of the original study. Evidence of full measurement invariance across gender and partial measurement invariance across age were obtained. These findings suggest that the Italian version of the EQ is a valuable tool for assessing flexibility about existential issues.